2021
DOI: 10.1002/ejhf.2191
|View full text |Cite
|
Sign up to set email alerts
|

Prospective ARNI vs. ACE inhibitor trial to DetermIne Superiority in reducing heart failure Events after Myocardial Infarction (PARADISE‐MI): design and baseline characteristics

Abstract: Patients surviving an acute myocardial infarction (AMI) are at risk of developing symptomatic heart failure (HF) or premature death. We hypothesized that sacubitril/valsartan, effective in the treatment of chronic HF, prevents development of HF and reduces cardiovascular death following high-risk AMI compared to a proven angiotensin-converting enzyme (ACE) inhibitor. This paper describes the study design and baseline characteristics of patients enrolled in the Prospective ARNI vs. ACE inhibitor trial to Determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 34 publications
(74 reference statements)
1
83
0
5
Order By: Relevance
“… 21 The PARADISE‐MI trail, aiming to ascertain whether sacubitril/valsartan prevents the development of HF and reduces cardiovascular deaths when compared with a previously proven ACEI/ARB among AMI patients, has also been recently released, although without reaching its primary endpoint. 15 In our study, it is shown that ARNI offers incremental clinical value for the prevention of cardiovascular death. The difference of our results might be because the primary endpoints of our study include the first onset as well as the recurrence of heart failure.…”
Section: Discussionmentioning
confidence: 62%
“… 21 The PARADISE‐MI trail, aiming to ascertain whether sacubitril/valsartan prevents the development of HF and reduces cardiovascular deaths when compared with a previously proven ACEI/ARB among AMI patients, has also been recently released, although without reaching its primary endpoint. 15 In our study, it is shown that ARNI offers incremental clinical value for the prevention of cardiovascular death. The difference of our results might be because the primary endpoints of our study include the first onset as well as the recurrence of heart failure.…”
Section: Discussionmentioning
confidence: 62%
“…Considering that Sacubitril/ Valsartan could inhibit the activation of RAAS, many researchers hypothesized that Sacubitril/Valsartan have benefits in patients after AMI. 20,21 For these patients, there were still confusions about the benefits and risks of Sacubitril/Valsartan and ACEI. After a comprehensive search and strict screening, a total of four studies involving 6154 patients were included.…”
Section: Discussionmentioning
confidence: 99%
“…The design and baseline characteristics of the PARADISE-MI trial have been published. 21 The primary results of the PARADISE-MItrial were presented at the American College of Cardiology's 70th Annual Scientific Session, 17 but they have not been formally published in sources such as books or journals. After discussion, the PARADISE-MI trial has been considered eligible to be included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Sacubitril/valsartan also significantly decreased plasma NT-proBNP and reverted clinical features of cardiac remodeling (i.e., improved LVEF and cardiac volume) in HFrEF patients with and without type-2 diabetes mellitus in the PROVE-HF registry [21]. However, sacubitril/valsartan was not significantly different from valsartan alone in reverting structural remodeling in patients with asymptomatic post-myocardial infarction (MI) LV systolic dysfunction [22], although the efficacy of ARNI in this subset of patients is still being investigated in the PARADISE-MI trial [23]. Sacubitril/valsartan significantly lowered cardiovascular mortality, improved clinical outcomes (e.g., rehospitalization) and markedly reduced plasma NT-proBNP concentration, without major adverse events in acute decompensated HF, irrespective of the HF history or prior treatment with RAAS blockers [24,25].…”
Section: Heart Failurementioning
confidence: 99%